Lusophone community in the digital age: the ambiguous place of scepticism and performance - Sousa, Helena (2018)
(Excerto) "This article addresses the setting up of the political Community of the Portuguese Language Countries (Comunidade dos Países de Língua Portuguesa (CPLP)) and its present-day social and cultural dynamics. As the other articles in this Special Section from Martins, Salgado and Santos also demonstrate, media and communication systems are playing a role in the development of this loose aggregation and in the internal dynamics of the Portuguese language countries."